If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 2y = -9 Solving -15 + 2y = -9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 2y = -9 + 15 Combine like terms: -15 + 15 = 0 0 + 2y = -9 + 15 2y = -9 + 15 Combine like terms: -9 + 15 = 6 2y = 6 Divide each side by '2'. y = 3 Simplifying y = 3
| (7x+1)=29 | | 7x^4+21x^3+14x^2=0 | | Sec^2x+tanx=7 | | 3(z+10)+z=98 | | 90=(4w-9)w | | 12+37x=5 | | 7n-5=6 | | 240+20h=980 | | (5p-7)^1/3=2 | | m=5(4+m)+2 | | 17.90+15.25h=109.40 | | 8j-31=13-3j | | 9e^4x=729 | | 5v^2=13v+6 | | (8x-9)/5 | | 5x-2(-x+18)=34 | | 8x-9/5 | | 7x^2-6=-14 | | 3p-15=49 | | -4(3x+2)=3(6x+-6) | | 24x^18/4x^2 | | 7+9x-29+63x=72+32x | | y+3x=480 | | 3x1/6= | | (x+40000)*.02= | | 240b+83=73 | | (13z^9+6v)11z^9= | | 11=7x-2(4x-3) | | 240b-83=73 | | 12x2-7x-11/7x-2 | | (21)6-15=8 | | 2x-9+x=10-5x-3 |